'Our patience has run out'tracking the anti-government protest cycle in Bulgaria. Issue 4 (2nd October 2019) - O'Brien, Thomas
ABSTRACT: The increase in protest intensity that Bulgaria experienced over the 2012–14 period had dramatic effects, bringing down a government and maintaining pressure on its successor. These protests started with a campaign over high energy prices, but grew and shifted to address broader issues of governance, encapsulated in slogans such as '24 years of fake transition are enough.' Dramatic though they were, the lasting effects are unclear in environment where the legacies of the communist regime led to a weak civil society and low levels of trust. This paper uses a unique catalogue of protest events over the 2010–2016 period to identify the character and form of protest observed in Bulgaria. Drawing on Tarrow's concept of protest cycles, the aim is to determine why the protests grew and whether there may be more lasting effects after they subsided. The findings point to the importance of the longevity of the cycle in creating spaces for the establishment of social relations that may have more lasting effects.